Komunikasi Interpersonal Pegawai Kantor Kelurahan Terondol Kecamatan Serang dalam Meningkatkan Pelayanan Publik - Shafira Dwiyanti; Rizqi Fitrianti; Arfian Suryasuciramdhan; Achmad Nashrudin Priatna; Meiby Zulfikar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Public services at the village level are the starting point for interaction between the government and the community. Problems that often arise, such as a lack of professionalism among officials, misunderstandings, and unclear information, can lead to public dissatisfaction. This study aims to identify the forms of interpersonal communication used by Terondol Village officials in public services, as well as the communication strategies used to handle complaints. Using descriptive qualitative methods through interviews, observations, and documentation with 1 key informant and 3 secondary informants, the study found that officials use friendly, open communication that is tailored to the character of the local community. Communication strategies include empathy, the use of simple language, and the delivery of clear and transparent solutions. Good communication has been proven to build trust, increase satisfaction, reduce conflict, and strengthen the image of the institution. This study confirms that interpersonal communication plays a significant role in the success and improvement of public service quality at the village level. Furthermore, the study highlights the importance of adapting communication strategies to the needs and expectations of the community. Therefore, the application of effective communication strategies that align with the characteristics of the community is a key factor in creating better and more satisfying public services. The findings suggest that strengthening communication training for village officials could further enhance service delivery and community engagement.